The Role of Physical Education on Motivation, Engagement, Sport Satisfaction, and Health-Related Fitness of High-School Students - Maryam Abdoshahi; Afsaneh Shemshaki (Shiraz University of Medical Sciences, 2021)
Background: Students' participation in sports activities in the course of physical education is essential for their health and may be influenced by the teacher's instructing strategies. The present research aimed to examine the effect of a self-determined intervention in physical education class on motivation, engagement, sport satisfaction, and health-related physical fitness of adolescent students. Methods: The present study employed a causal-comparative approach and was conducted on 80 high-school girls (mean age of 16.63 years) of Tehran, Iran, 2019, who were randomly allocated into two intervention and control groups. The students in the intervention group were exposed to a three-month self-determined-based intervention within the physical education class adopted by the teacher. On the other hand, those in the control group attended their regular physical education class. A standard questionnaire assessed the motivation, engagement, and sport satisfaction. Field tests evaluated physical fitness, comprising agility and cardiorespiratory fitness. Independent t-test and ANCOVA were employed for data analysis. Results: The findings demonstrated that compared to traditional teaching, self-determined intervention contributed to a significantly higher level of motivation (3.58±0.66, p <0.001), engagement (3.14±0.49, p <0.001), and sport satisfaction (2.71±0.20, p <0.001) in the post-test. Our results also revealed that exposure to a self-determined intervention did not significantly improve health-related physical fitness components, including agility (P=0.489) and cardiovascular fitness, (P=0.561) compared to nonautonomous training. Conclusion: These findings may indicate that the feeling of autonomy, competence, and relatedness within physical education class encompasses greater effects on psychological factors (motivation, intention to engagement, and satisfaction) than physical factors (physical fitness).